2013
DOI: 10.1128/jvi.02506-12
|View full text |Cite
|
Sign up to set email alerts
|

Toscana Virus NSs Protein Promotes Degradation of Double-Stranded RNA-Dependent Protein Kinase

Abstract: Toscana virus (TOSV), which is transmitted by Phlebotomus spp. sandflies, is a major etiologic agent of aseptic meningitis and encephalitis in the Mediterranean. Like other members of the genus Phlebovirus of the family Bunyaviridae, TOSV encodes a nonstructural protein (NSs) in its small RNA segment. Although the NSs of Rift Valley fever virus (RVFV) has been identified as an important virulence factor, which suppresses host general transcription, inhibits transcription from the beta interferon promoter, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 35 publications
(51 reference statements)
1
45
1
Order By: Relevance
“…We previously reported that rMP-12 carrying the Toscana virus (TOSV) NSs increases the neuroinvasion of rMP-12 in mice (death rate, ϳ36%) (68). TOSV NSs inhibits the IFN-␤ promoter and promotes the degradation of PKR, yet it does not suppress host general transcription (75). This indicates that the quality of the host antiviral response in target cells influences the neuroinvasion of RVFV.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that rMP-12 carrying the Toscana virus (TOSV) NSs increases the neuroinvasion of rMP-12 in mice (death rate, ϳ36%) (68). TOSV NSs inhibits the IFN-␤ promoter and promotes the degradation of PKR, yet it does not suppress host general transcription (75). This indicates that the quality of the host antiviral response in target cells influences the neuroinvasion of RVFV.…”
Section: Discussionmentioning
confidence: 99%
“…TOSV NSs has been shown to possess two distinct functions: (i) to limit IFN-␤ upregulation (Gori Savellini et al, 2001) and (ii) to promote RNA-dependent protein kinase degradation (Kalveram and Ikegami, 2013). Further studies will be necessary to understand if and how these phosphorylation sites are involved in these functions.…”
Section: Resultsmentioning
confidence: 98%
“…28,29,32 We assume that RVFV NSs functions, such as general transcription suppression, PKR degradation, or IFN-b suppression, coordinately support efficient RVFV replication and spread in liver tissues, and thus, the spreads of rZH501-TOSNSs and rZH501-SFSNSs were more restricted than parental rZH501 in mouse livers.…”
Section: Discussionmentioning
confidence: 99%
“…The NSs gene of ZH501 S-segment in the pProT7-wS(C) plasmid were replaced with NSs open-reading frame (ORF) of TOSV (ISS. Phl.3), SFSV (Sabin), PTA (TVP10208), PTB (TVP13993), or PKRDE7, as described previously 13,30,32,33 to rescue rZH501-TOSNSs, rZH501-SFSNSs, rZH501-PTANSs, rZH501-PTBNSs, or rZH501-PKRDE7, respectively. To generate rZH501-DNSs16/198 or rZH501-DNSm21/384, corresponding regions in the S-, or M-segment were deleted by site-directed mutagenesis using pProT7-wS(C) or pProT7-wM(C) plasmids, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation